IbM KELOMPOK USAHA BATIK DI KELURAHAN SUTOREJO KOTA SURABAYA - Sumiati .; Yuliar Kartika; Siti Mujanah (JPM17: Jurnal Pengabdian Masyarakat, 2017)
The purpose of this study is to develop of new Entrepreneur of the Housewives inSutorejo village, Surabaya Municipality, Indonesia. This study began by providingequipment and batik materials, than training of batik design and coloring as well asbusiness management so that the partners of this study becomes an entrepreneur, so thatcould generate additional income in the prosperous family. This activity is aimed athousewife in Sutorejo village, Mulyorejo Sub-district with name "Group of Serasi 1 andSerasi Group 2" which has the number of members as many as 16 people each group,Previously they did batik in Village office with equipment in turn because there are onlyfew of tools used by all members, and they have minimal of skills especially indesigning, coloring, and business management.This Community Partnership Program (PKM) is done by providing equipment andmaterials as well as training in the field of batik with the design and coloring thatcharacterizes its own as a batik icon that will be in the production of the Serasi group.Moreover, the purpose of this activity is to prepare them as SMEs which capable toproduct, sell and well manage the business appropriately, they must have knowledge inthe field of management, especially business management, Marketing and managingfinance. With equipment, competence on designing batik with coloring techniques andmanagement skill they able to produce and sell batik product to earn income.Keywords: Enterprenuer, Batik Design, Batik Coloring, and Business Management